5x-3=6-2x

Simple and best practice solution for 5x-3=6-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=6-2x equation:


Simplifying
5x + -3 = 6 + -2x

Reorder the terms:
-3 + 5x = 6 + -2x

Solving
-3 + 5x = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + 5x + 2x = 6 + -2x + 2x

Combine like terms: 5x + 2x = 7x
-3 + 7x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + 7x = 6 + 0
-3 + 7x = 6

Add '3' to each side of the equation.
-3 + 3 + 7x = 6 + 3

Combine like terms: -3 + 3 = 0
0 + 7x = 6 + 3
7x = 6 + 3

Combine like terms: 6 + 3 = 9
7x = 9

Divide each side by '7'.
x = 1.285714286

Simplifying
x = 1.285714286

See similar equations:

| 25b^2-60b+36= | | -11m+(-6m)= | | -16m-(-38m)+12m= | | 1/5(3-6x)=1/30+x/2 | | 14+6y=8(y-1) | | -15=+(-5) | | 9-5x=3/4+12x | | 32k=896 | | -3x=.5 | | l^2-5l+6=0 | | 19+k=32 | | y/3=-19 | | 0.30x+0.05(20-x)=0.10(25) | | 8(h+2)-5(h-1)=6h | | 2x^2+40x+180=0 | | 5y+2y(y-6)=4(y+1)-2 | | X+3/4x=84 | | 10x-41=69 | | 9t-16r=-49 | | 2x^3-40x+192xy^2=0 | | x^2-2*435*x+(2*11.637*(10^6))/(0.9*0.85*20.7*800)=0 | | x^2-2*435*x+2*11.637*10^6/0.9*0.85*20.7*800=0 | | x^2-2*435*x+2*11.637/0.9*0.85*20.7*800=0 | | -4*5-4y=16 | | -3(2x+1)=x+9 | | 9*3+9y=81 | | 2(k+2)+6(k-2)=5k-2 | | .5t+15=-10 | | (7x-3)(12x-7)= | | -(2x+3)=3x+1 | | (3x-5)=2.5x+3(x-6) | | 1-10/13 |

Equations solver categories